2020
DOI: 10.1016/j.celrep.2019.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Specific Ion Channels Control Sensory Gain, Sensitivity, and Kinetics in a Tonic Thermonociceptor

Abstract: Pain sensation and aversive behaviors entail the activation of nociceptor neurons, whose function is largely conserved across animals. The functional heterogeneity of nociceptors and ethical concerns are challenges for their study in mammalian models. Here, we investigate the function of a single type of genetically identified C. elegans thermonociceptor named FLP. Using calcium imaging in vivo, we demonstrate that FLP encodes thermal information in a tonic and graded manner over a wide thermal range spanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 55 publications
6
28
0
Order By: Relevance
“…The time-lapse recordings were analyzed using LAS X software (Leica), adapting a previously described method 65 . Briefly, two regions of interest (ROI) were selected for each cell, and 50 cells per plate were chosen randomly.…”
Section: Methodsmentioning
confidence: 99%
“…The time-lapse recordings were analyzed using LAS X software (Leica), adapting a previously described method 65 . Briefly, two regions of interest (ROI) were selected for each cell, and 50 cells per plate were chosen randomly.…”
Section: Methodsmentioning
confidence: 99%
“…Ford et al (2018) reported that NALCN may contribute to neuronal excitability of spinal projection neurons. Additionally, the C. elegans NALCN gene, NCA-1, controls the thermal sensitivity of thermo-nociceptor and NCA-2 functions in thermal sensitivity, sensory gain maintenance, and signal kinetics during thermal stimuli termination (Saro et al, 2020). Eigenbrod et al (2019) showed that highveld mole-rat cells that expressed the NALCN gene produced a depolarized RMP to about −20 mV, which may induce a state unresponsive to normal stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The time-lapse recordings were analyzed using LAS X software (Leica), adapting a previously described method 72 . Brie y, two regions of interest (ROI) were selected for each cell, and 50 cells per plate were chosen randomly.…”
Section: Fret Imaging Analysismentioning
confidence: 99%